Conceptualisation Du Consentement Dans L’arbitrage D’investissement Encadré Par Le Cirdi - Jean Marie Barambona; Anaclet Nzohabonayo (European Scientific Journal, ESJ, 2018)
The Convention on the Settlement of Investment Disputes between States and Nationals of Other States is a founding legal instrument for the management of investment arbitrations supervised by ICSID. The merit of ICSID arbitral tribunals is conditioned on the expression of the consent of the host State and the foreign investor. While a consensus has emerged on how to consent to these types of arbitrations, the issue of consent survival is gaining momentum and the ongoing debate does not offer a common understanding. The renewed interest, which puts this issue at the center of the debate, is fueled by denunciations of bilateral investment treaties while investors under their protection continue to conduct their economic operations in the denouncing country. This analysis is aimed to contribute to the ongoing debate by examining the effects of these denunciations on the survival or not of the host state consent on investment arbitration. More importantly, the consent constitutes a key element without which the protection due to the admitted investments in the host territory would be defeated. Before turning to this issue, we first examine the different ways parties to the investment arbitration express their consent to the ICSID investment arbitration.